Classification of solar panel technology and photovoltaic cell status applying machine learning to electroluminescence images - (:unkn) unknown (IEEE, 2024)
Photovoltaic energy, being renewable and environmentally friendly, significantly contributes to reducing greenhouse gas emissions. Its popularity and swift technological advances have facilitated the widespread commercialization of solar panels across va...
Keywords: Paneles solares; Aprendizaje automático